Self-esteem Pada Penyandang Disabilitas Fisik Pasca Kecelakaan - Aji Putra (Academica : Journal of Multidisciplinary Studies, 2018)
AbstractPeople with disabilities often experience feelings of inferiority in their community. This makes people with disabilities often depressed or have difficulty accepting the situation. So there is need for rehabilitation to encourage and provide some provisions for their lives. The purpose of this study was to find out how the process of developing self-esteem of persons with physical disabilities through social rehabilitation at BBRSBD Prof. Dr. Soeharso Surakarta. The method in this research is descriptive qualitative method by conducting several observations and interviews. The results obtained, that the process of self-development or self-esteem carried out at BBRSBD Prof. Dr. Soeharso Surakarta, the initial stage is the concept of self-mirror. Then given some motivation and skills that are able to awaken themselves and equip themselves in their lives.Keywords: Disability, self-esteem